The Increased Sex Differences in Susceptibility to Emotional Stimuli during Adolescence: An Event-Related Potential Study - Yang, Jiemin; Zhang, Shu; Lou, Yixue; Long, Quanshan; Liang, Yu; Xie, Shixue; Yuan, Jiajin (Frontiers in Human Neuroscience, 2018)
The present study investigated how pubertal development and sex interact to influence humans’ emotion susceptibility during adolescence. Event-related potentials were recorded for highly emotional, mildly emotional, and neutral stimuli in positive and negative blocks, when seventy-three adolescents (36 pre-/early pubertal students, 19 boys, 10-12 years old; 37 mid-/late pubertal students, 18 boys, 11-13 years old) performed an implicit emotion task. Behavioral analysis showed higher positive mood ratings for pre-/early compared to mid-/late pubertal subjects, irrespective of sex and block. ERP analysis demonstrated increasing Late Positive Potential (LPP) amplitudes from neutral, MP to HP stimuli in pre-/early pubertal, but not in mid-/late pubertal adolescents. However, girls exhibited higher P3a amplitudes during mid-/late relative to pre-/early puberty for negative stimuli irrespective of intensity; while this puberty effect was absent in boys. In addition, regardless of pubertal stage, girls exhibited a more pronounced LPP enhancement effect for HN stimuli, and a lower threshold of responding to negative stimuli in P3b amplitudes compared to boys. These results suggest that though there is a puberty-independent sensitivity to negative stimuli in girls relative to boys, puberty selectively intensifies girls’ attention bias for negative stimuli and reduces experiential sensitivity to positive stimuli in both sexes. The implication of these results for the sex-related psychopathology during adolescence were discussed.